2014
DOI: 10.1002/hipo.22242
|View full text |Cite
|
Sign up to set email alerts
|

Subregion‐specific decreases in hippocampal serotonin transporter protein expression and function associated with endophenotypes of depression

Abstract: Stress influences the development of depression, and depression is associated with structural and functional changes in the hippocampus. The current study sought to determine whether chronic corticosteroid (CORT) treatment influences serotonin transporter (5-HTT) protein expression and function in the CA1, CA3, and dentate gyrus (DG) subregions of the hippocampus. Male CD-1 mice were subcutaneously injected with CORT at a dose of 20 mg/kg once daily for 3 weeks. Behavioral state was assessed using sucrose pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 79 publications
2
20
1
Order By: Relevance
“…Since FGF22 is required for normal excitatory synapse development in the hippocampus, and the hippocampus has been implicated in affective behaviors modeled by the forced swim and tail suspension tests (28, 29), our results are consistent with the hypothesis that loss of excitatory synapses in the hippocampus is responsible for the altered behaviors observed in FGF22KO mice, including a passive style of coping with stress and anhedonia. Of course, it is also possible that there are other brain regions involved in the behaviors we observed, such as the prefrontal cortex (30-32), and we are currently investigating the neural circuits that may be involved in the behavioral manifestations of FGF22 deletion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Since FGF22 is required for normal excitatory synapse development in the hippocampus, and the hippocampus has been implicated in affective behaviors modeled by the forced swim and tail suspension tests (28, 29), our results are consistent with the hypothesis that loss of excitatory synapses in the hippocampus is responsible for the altered behaviors observed in FGF22KO mice, including a passive style of coping with stress and anhedonia. Of course, it is also possible that there are other brain regions involved in the behaviors we observed, such as the prefrontal cortex (30-32), and we are currently investigating the neural circuits that may be involved in the behavioral manifestations of FGF22 deletion.…”
Section: Discussionsupporting
confidence: 87%
“…In this test, animals are provided with both water and 2% sucrose solution for several days to measure the degree of their preference for sucrose over water. Typically, mice prefer sucrose at a very high ratio (28). Using a separate cohort of experiment-naïve mice, we observed that WT mice demonstrate a significant preference for sucrose over water, whereas FGF22KO animals prefer sucrose to a lower extent, consistent with lack of pleasure-motivated behavior or anhedonia (Student's unpaired two-tailed t -test, t(29)=4.66, p<0.0001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The 5-HT system is highly interactive with other biological systems. Being one of the brain areas implicated in MDD, the hippocampus may have a particular role in the interactions between the 5-HT system and the hypothalamic-pituitary-adrenal (HPA) axis [ 27 , 45 ]. Lower mRNA expression of cortisol-inducible genes, which can be seen as a marker for a blunted cortisol response, was previously found to be associated with smaller hippocampal volumes in MDD patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…data to the Michaelis-Menten equation as previously described (Tang et al, 2014). Values of both parameters are shown in Table 2.…”
Section: Strain Differences In 5-htt Protein Expression In Each Hippomentioning
confidence: 99%
“…For synaptosomal 5-HT uptake, V max is positively related to the total number, and K m is negatively related to the uptake efficiency, of the membrane-bound 5-HTT, respectively (Ansah et al, 2003;Zhu et al, 2010;Hagan et al, 2012;Tang et al, 2014). Our data showed that DBA mice showed a higher V max and a lower K m , indicating that the mice not only had more membrane-bound 5-HTT, but also had higher uptake efficiency in all three hippocampal subregions compared to the other three mouse strains (Fig.…”
Section: Strain Differences In 5-htt Protein Expression In Each Hippomentioning
confidence: 99%